MR outcome parameters in multiple sclerosis: comparison of surface-based thresholding segmentation and magnetization transfer ratio histographic analysis in relation to disability (a preliminary note). - van Waesberghe, J H; van Buchem, M A; Filippi, M; Castelijns, J A; Rocca, M A; van der Boom, R; Polman, C H; Barkhof, F (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSES MR imaging is now widely used to monitor disease progression in patients with multiple sclerosis (MS). The purpose of this study was to explore the relationship between disability status and existing and new MR parameters in MS patients.METHODS Forty-one patients with clinically definitive MS were studied. MR imaging included T2- and T1-weighted imaging as well as gradient-echo imaging with and without magnetization transfer contrast. We used surface-based thresholding segmentation techniques to obtain T2 and T1 lesion load, T1/T2 ratio, and several magnetization transfer ratio (MTR) lesion load parameters. MTR histographic analysis included measurements of absolute peak height (aHp), relative peak height (rHp), MTR of the peak (MTRp), mean MTR (MTRm), and MTR25, MTR50, and MTR75, relating to the integrals of the histogram at 25%, 50%, and 75%, respectively, of the total area under the curve. All MR parameters were correlated with Expanded Disability Status Scale (EDSS) score, disease duration, and patient's age.RESULTS Using surface-based thresholding segmentation techniques, we found relatively low correlations with EDSS. T1 lesion load and T1/T2 ratios correlated most strongly. Regarding MTR histographic parameters, EDSS correlated best with rHp but only weakly with others. Similar correlations were found with disease duration, but not with age.CONCLUSION The best MR correlations with disability were several MTR histographic parameters. Our findings may favor the use of these MR parameters over T2 lesion load to monitor disease progression in patients with MS, findings that should be explored further in longitudinal studies.